Validation study of a 15-plex rapid STR amplification system for human identification. (May 2017) - Han, Junping; Sun, Jing; Zhao, Lei; Zhao, Wenting; Liu, Yao; Li, Caixia
Highlights: We explore a rapid 15-plex PCR system which could shorten the amplification time to 37 min. The performance of this system, including sensitivity, species specificity, stability tests, sizing accuracy, stutter calculation, concordance tests, DNA mixture, and case sample tests, is satisfied with the Scientific Working Group for DNA Analysis Methods (SWGDAM) guidelines and Chinese criteria. This system provides an alternative method for conventional PCR in human identification detection. Abstract: Conventional PCR amplification requires approximately 3 h to complete and thus does not meet the requirements of rapid DNA analysis. The purpose of this study was to validate a rapid 15-plex PCR system that can amplify 14 autosomal short tandem repeat (STR) loci ( i.e., D6S1043, D21S11, D7S820, CFS1PO, D2S1338, D3S1358, D13S317, D8S1179, D16S539, Penta E, D5S818, vWA, D18S51, and FGA) and Amelogenin. This system was validated by sensitivity, species specificity, inhibitor tests, sizing accuracy, stutter calculation, concordance tests, DNA mixture, and case sample tests according to the Scientific Working Group for DNA Analysis Methods (SWGDAM) guidelines and Chinese criteria. We found that the rapid 15-plex PCR system could shorten the amplification time to 37 min and proved that it provides an alternative method for conventional PCR in human identification detection.